Growing up prairie: ecological drivers of grassland songbird nestling development - Winnicki, Sarah (Kansas State University, 2019)
Animals develop at different rates and require differing amounts of parental investment, yet the drivers of both inter- and intraspecific variation in growth are often unclear. In altricial birds, both food delivery by parents and nest predation risk are known to influence developmental strategies, but until now, it has been unclear how brood parasitism might influence host development. I studied interactions between brood parasitic Brown-headed Cowbirds (Molothrus ater) and three grassland-obligate songbirds at the Konza Prairie in Northeast Kansas. My three focal host species ranged in size from ~40% to 270% of cowbirds’ mass: large Eastern Meadowlarks (Sturnella magna), medium-sized Dickcissels (Spiza americana), and small Grasshopper Sparrows (Ammodramus savannarum). We hypothesized that brood parasitism by cowbirds would influence inter- and intraspecific development variation (1) directly by exacerbating costly sibling competition and/or (2) indirectly by interacting with other environmental drivers like predation risk and food availability. Additionally, we hypothesized that (3) host species, nest-specific food provisioning rate, and spatial variation in predation risk would influence intra-specific cowbird nestling growth. I located and monitored 148 nestling-stage nests over two years, and measured the growth of 316 host nestlings’ and 54 cowbird nestlings’ tarsi, wings, mass, bills, and feathers every two days to quantify overall growth and the allometric scaling of structures associated with nestling competition and post-fledging mobility. Variation in host nestling development exhibited species-specific responses to cowbird parasitism; meadowlarks left the nest earlier than conspecifics in unparasitized nests, Dickcissel nestlings grew more slowly, and Grasshopper Sparrow nestlings were not directly affected by the presence of brood parasites. Brood parasitism was also associated with key drivers of nestling development including nest predation risk and provisioning rate. However, considerable variation in host growth appeared to be shaped by individual variation in parental care. Cowbird nestling mass gain and the allometric scaling of body parts associated with nestling competition varied among host species, and was associated with provisioning rate and brood size. Overall these results demonstrate that inter- and intraspecific variation in growth and development can be extremely high, even at a single site. Additionally, brood parasitism can have species- and nest-specific consequences attributable in part to individual parental behavior. These results provide insight into the relationship between a declining guild of grassland songbird host species and the native brood parasites with which they have interacted for millennia, and helps interpret host-parasite interactions in novel contexts.
Keywords: Development; Brood parasitism; Birds; Nestling; Allometry; Growth rate